DIMENSIONS OF RELIGIOSITY IN ABIDAH EL KHALIEQY'S NOVELS - Abid Sahulata Lingga Sakti; Riswanda Himawan (Literature and Literacy, 2024)
Literary works can depict various phenomena from various sectors, including cultural, social, political, psychological, and religious. Interestingly, in the research of literary works and religion, it is often distinguished between religion and non-religion, even though religion in literary works is universal. Therefore, this study aims to explain the dimensional aspects of religiosity in Abidah El Khalieqy's novels. The type of research is descriptive qualitative, using the religiosity theory approach by Glock and Stark. The data sources of this research are the novels Geni Jora, Mataraisa, Bait-Bait Multazam, and Santri Cengkir. Data collection uses reading and note-taking techniques, while this study uses human interest. Data validity is interrater and interrater techniques. Data analysis uses the method of comparing data, categorizing, presenting data, and making inferences. The results of this study show that religiosity in Abidah El Khalieqy's novels related to the five dimensions of Glock and Stark consists of a belief dimension, a belief practice dimension, a science dimension, an experience dimension, and an experience effect dimension. The conclusion explains that Glock and Stark's multidimensional typology of religiosity dimensions is universal in the treasures of Islamic culture. The problem presented in the novel is the problem between characters in achieving the lost dimension of religiosity, which functions as a human value and transcendence in obtaining the lost dimension in life.